2021
DOI: 10.1186/s13567-021-01007-8
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and local host response following intramammary Staphylococcus chromogenes challenge in dry cows

Abstract: Although extensive research has been performed on bovine non-aureus staphylococci (NAS), several aspects such as bacteria-host interaction remain largely unstudied. Moreover, only a few mastitis pathogen challenge studies in cows have been conducted in the dry period, an important period that allows intramammary infection (IMI) to cure and new IMI to occur. We challenged 16 quarters of 4 Holstein Friesian cows at dry off with 100; 100 000 or 10 000 000 CFU of the udder-adapted S. chromogenes IM strain. Four qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…On the other hand, our research also revealed the limits of S. chromogenes IM as a potential priming agent against S. uberis mastitis. Likewise observed in dairy cows [ 13 ], S. chromogenes IM induces mastitis in the murine mammary gland. Indeed, the observed influx of polymorphonuclear immune cells and significantly increased levels of proinflammatory mediators IL-8 and LCN2 support this latter statement.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…On the other hand, our research also revealed the limits of S. chromogenes IM as a potential priming agent against S. uberis mastitis. Likewise observed in dairy cows [ 13 ], S. chromogenes IM induces mastitis in the murine mammary gland. Indeed, the observed influx of polymorphonuclear immune cells and significantly increased levels of proinflammatory mediators IL-8 and LCN2 support this latter statement.…”
Section: Discussionmentioning
confidence: 83%
“…These effects have been related to bacterial secreted mediators such as bacteriocins and other potentially beneficial mechanisms such as priming of the immune system [ 9 , 11 ]. We previously showed that S. chromogenes IM, a bovine-derived mastitis strain, is able to (i) inhibit the in vitro growth of major mastitis pathogens including S. uberis and (ii) colonize the bovine mammary gland in vivo [ 12 , 13 ]. To better understand whether priming the mammary gland with S. chromogenes IM inhibits the growth of S. uberis , mouse experiments were hereafter conducted in which S. chromogenes IM-primed murine mammary glands were challenged with S. uberis .…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that respect, NAS might provide protection against intramammary infection (IMI) with major mastitis bacterial pathogens [13,14]. Over the years, our research group has reported multiple findings substantiating, to some extent, the latter concept [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%